Subsurface ocean warming preceded Heinrich Events - Lars Max; Dirk Nürnberg; Cristiano M. Chiessi; Marlene M. Lenz; Stefan Mulitza (Nature Communications, 2022)
The mechanism driving past Laurentide Ice-Sheet instabilities remains elusive Here, the authors present a sediment record from the subpolar western North Atlantic and show that massive warming of the upper interior ocean was the likely trigger for repeated collapses of the Laurentide Ice-Sheet and iceberg discharge into the North Atlantic, known as Heinrich Events.